Regulation of Murine Natural Killer Cell Development - Goh, Wilford; Huntington, Nicholas D. (Frontiers in Immunology, 2017)
Natural killer (NK) cells are effector lymphocytes of the innate immune system that are known for their ability to kill transformed and virus-infected cells. NK cells originate from hematopoietic stem cells in the bone marrow and we have learnt a great deal about both cell intrinsic and extrinsic factors required for their survival and normal development in recent years. The development of NK cells can be broadly categorised into two phases: lineage commitment and maturation. Efforts to better define the developmental framework of NK cells have led to the identification of several NK progenitor populations and mature NK cell subsets, each defined by a varied set of cell surface markers. The relationship between some of these NK cell subsets remains to be determined. NK cell maturation is associated with the acquisition of effector functions such as cytokine production and target cell killing. Consequently, the factors that regulate NK cell development and function are of particular interest as these factors could potentially be targeted in NK-cell based immunotherapeutics. The classical approach to studying both NK cell development and function is to identify the transcription factors involved and elucidate the mechanistic action of each transcription factor. In this regard, recent studies have provided further insight into the mechanisms by which transcription factors such as ID2, FOXO1, KLF2 and GATA3 regulate various aspects of NK cell biology. It is also becoming evident that the biology of NK cells is not only transcriptionally regulated, but also determined by epigenetic alterations and post-transcriptional regulation of gene expression by microRNAs. This review summarises recent progress made in NK development, focusing primarily on transcriptional regulators and their mechanistic actions.